Kelelahan Emosional dalam Relasi Pertemanan Remaja Berlatar Budaya Kolektivistik: Analisis Kasus dan Penerapan Strategi Konseling Berwawasan Budaya Indonesia - Yetti Murniati; Fadhilla Yusri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Emotional exhaustion in the context of adolescent friendships is a phenomenon that is often overlooked in the counseling literature, particularly when analyzed through the lens of Indonesia’s collectivist culture. This study aims to conduct an in-depth analysis of the dynamics of emotional exhaustion experienced by a 21-year-old female adolescent due to relational imbalance in a three-year-long friendship, as well as to describe the application of Indonesian culture-sensitive counseling strategies as an intervention effort. Using a qualitative research method with a single-case study design, data were collected through in-depth interviews, observation of counseling sessions, and analysis of documentation. The findings identified six main problem dimensions: relational imbalance, chronic emotional exhaustion, unmet emotional needs, emotional withdrawal, ambivalence, and a deficit in assertive communication. Collectivist cultural values particularly modesty, social harmony, and friendship loyalty were found to exacerbate emotional exhaustion by inhibiting the expression of personal needs. An intervention combining culturally adapted Person-Centered Therapy (PCT) and Cognitive Behavior Therapy (CBT), including the application of assertiveness training based on local values and a consensus-building approach, demonstrated high responsiveness to the clients’ cultural context. This study contributes to the development of a more context-specific cross-cultural counseling model for Indonesian adolescents.